Summary of the R/V Mirai Arctic Ocean cruise in 2020 - Nishino, Shigeto; Fujiwara, Amane; Itoh, Motoyo; Onodera, Jonaotaro; Murata, Akihiko; Kikuchi, Takashi (2020)
The 11th Symposium on Polar Science/Special session: [S] Accelerating Arctic research: Recent progress and future prospect of Arctic research, Poster presentations, Mon. 16 Nov. - Fri. 18 Dec. conference object